Persepsi Positif Orang Tua Balita terhadap Minat dalam Penggunakan CheckIT Moms - Ni Nyoman Ayu Desy Sekarini; Putu Irma Pratiwi; Anjar Tri Astuti (Indonesian Journal of Midwifery (IJM), 2022)
The developmental status of children under five in Indonesia still requires special attention where children who experience general developmental delays are quite high, reaching 5-10%. Various factors that influence child development include nutritional status, family economic status, parental education, and parental stimulation. The role of parents is the most influential thing in development, namely by doing detection and stimulation independently at home. However, many parents feel unable to do so, because of their ignorance and inability. So that a mobile application was developed to detect and stimulate children's development. This study aims to determine the effect of perceived benefits, convenience, security and risk on the interest of parents of toddlers using "CheckIT Moms". This research is an explanatory research with a quantitative analytic research design. This study used 221 parents with toddlers aged 0-60 months in Singaraja. The data collection technique used purposive sampling. The instrument used is a questionnaire of perceptions and interests filled out by respondents on a google form after using the "CheckIT Moms" application. Data analysis using multiple linear regression analysis method. The results showed that perceived benefits, perceived convenience, perceived risk and security had a positive effect on the use of the "CheckIT Moms" application with a constant value of 0.593 and a significant value of 0.002. Partial test using t-test of the benefit variable has a significant value of 0.00 < 0.05, which means that the perception of benefits has a positive effect on respondents' interest. The convenience variable has a significant value of 0.806 > 0.05, which means that the perception of convenience has no effect on respondents' interest. The risk and security variables have a significant value of 0.00 < 0.05, which means that the perception of risk and security has a positive effect on respondents' interest.Abstrak Status perkembangan balita di Indonesia masih memerlukan perhatian khusus dimana anak yang mengalami keterlambatan perkembangan umum cukup tinggi yaitu mencapai 5-10%. Berbagai factor yang mempengaruhi perkembangan anak meliputi status gizi, status ekonomi keluarga, pendidikan orang tua, dan stimulasi orang tua. Peran orang tua merupakan hal yang paling berpengaruh dalam perkembangan yaitu dengan melakukan deteksi dan stimulasi secara mandiri dirumah. Namun banyak orang tua merasa tidak mampu melakukannya, karena ketidaktauan dan ketiadakmampuan orang tua. Sehingga dikembangkan suatu aplikasi mobile mendeteksi dan menstimulasi perkembangan anak. Pada penelitian ini bertujuan untuk mengetahui Pengaruh Persepsi Manfaat, Kemudahan, Keamanan dan Resiko terhadap Minat Orang Tua Balita Menggunakan â€œCheckIT Momsâ€. Penelitian ini merupakan Explanatory Research dengan desain penelitian yaitu analitik Kuantitatif. Penelitian ini menggunakan 221 orang tua yang memiliki balita usia 0-60 bulan di Singaraja. Teknik pengambilan data menggunakan purposive sampling. Instrument yang digunakan adalah kuisioner persepsi dan minat yang diisi oleh responden pada google form setelah menggunakan aplikasi â€œCheckIT Momsâ€. Analisa data menggunakan metode analisis regresi linear berganda. Hasil penelitian diperoleh persepsi manfaat, persepsi kemudahan, persepsi resiko dan keamanan berpengaruh secara positif terhadap penggunaan aplikasi â€œCheckIT Momsâ€ dengan nilai konstanta 0,593 dan nilai signifikan yaitu 0,002. Secara uji Parsial dengan menggunakan t-tes variabel manfaat memiliki nilai signifikan 0,00 < 0,05 yang artinya persepsi manfaat berpengaruh positif terhadap minat responden. Variabel kemudahan memiliki nilai signifikan 0,806 > 0,05 yang artinya persepsi kemudahan tidak memiliki pengaruh terhadap minat responden. Variabel resiko dan keamanan memiliki nilai signifikan 0,00 < 0,05 yang artinya persepsi resiko dan keamanan berpengaruh positif terhadap minat responden.